Vocational Education: A Missing Link for the Competitive Graduates? - Sukardi; Wildan; Muh. Fahrurrozi (International Conference on Education, Islamic Studies and Social Sciences Research)
This study is based on the fact that the quality and competitiveness of vocational education graduates are still low. Therefore, this study was conducted to analyze the effectiveness of the implementation of vocational education by observing the relevance of the content with the issue or potential of the region( local area). This study uses a policy evaluation method formulated in the form of Service Quality (ServQual) by taking all vocational schools in 6 (six) sample districts/cities. The research instrument used is in-depth interview and document studies. The data were then analyzed using Location Quotient (LQ), growth ratio (MRP), and Overlay analysis. The results show that the content of vocational education reflected in the competence of skills developed was not relevant to the issues or potential of each district/city. This condition causes the low competitiveness of vocational education graduates, both in entrepreneurship and competing in the national and international labor market.